Confiabilidade de coroas com infraestrutura em zircônia sob fadiga deslizante: efeito do tipo de tratamento interno para cimentação - Monteiro, Evelyn Barbosa Carmona [UNESP] (2014)
The aim of the present study was to evaluate the fatigue life of zircônia crowns veneered with feldspathic porcelain. Sixty first molars were selected, prepared for full crown and divided into 3 groups according to surface treatment: primer (MDP); tribochemical silica coating (Rocatec Soft + silane); glaze (Vita Akzent + Hydrofluoric acid 10 % + silane). The veneering porcelain was applied respecting the anatomy of upper first molar. The zirconia inner surface was treated according to the group, cemented using resin cement. The specimens were cycled in sliding fatigue machine (200N, 3Hz), using a piston of 3.18 mm diameter, on the inner side of the mesial buccal cusp, until specimens fail or up to 2x106 cycles. Every 500,000 cycles, the specimens were evaluated for the presence of flaws in stereomicroscope (10 ×). To determine the probability of survival (reliability), Weibull analysis was performed, considering a two-sided confidence interval of 95 %. The predominant type of failure was cracking and chipping of the feldsphatic porcelain followed by delamination. Weibull parameters (beta and eta) for primer, silica coating and glaze groups were respectively 1,51 and 1,6.106 cycles; 1,50 and 0,739.106 cycles; 1,53 and 0,882.106 cycles. The reliability of all crowns decreased with time, but the crowns cemented with an MDP primer presented higher survival rates. Clinical Significance: The use on an MDP primer before cementation of a veneered zirconia crown can increase its tolerance to damage